Analisis Beban Pajak Tangguhan, Aktiva Pajak Tangguhan, Dan Akrual Sebagai Prediktor Manajemen Laba - Sari, Putri Indah Permata; Suripto, Suripto (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the information that always concerns every stakeholder is profit. This encourages companies (management) to display good financial performance, for example by doing earnings management. The purpose of this study is to determine and analyze Deferred Tax Expense, Deferred Tax Asset, and Discretionary Accrual on Earnings Management. The companies listed at Jakarta Islamic Index 70 constituent period December 2022 - May 2023 with the research period 2018-2021 are the population in this study. Sample determination using saturated sample technique. Panel data regression analysis using Eviews-9 was used for analysis methodologies and hypothesis testing. The findings indicated that Deferred Tax Assets had a negative impact on Earnings Management, while Accruals had a positive impact. However, Deferred Tax Expense partially had no impact on Earnings Management. Earnings management is simultaneously impacted by accruals, deferred tax assets, and deferred tax expenses.